توظيف البرامج التلفزيونية في معالجة جرائم العهنف الاسري - سمية طيبي; د/ علي ساحي (جامعة عمار ثليجي الاغواط, 2025)
تتناول هذه الدراسة موضوع توظيف البرامج التلفزيونية في معالجة جرائم العنف الأسري، باعتباره من المواضيع الحيوية والراهنة في المجتمع الجزائري، نظراً لتزايد حالات العنف داخل الأسرة، لا سيما ضد النساء والأطفال، وتنامي التغطية الإعلامية لهذه الظاهرة، خاصة عبر القنوات التلفزيونية الوطنية. وتهدف الدراسة إلى تحليل كيفية معالجة هذه الجرائم عبر البرامج التلفزيونية الاجتماعية، من خلال دراسة حالة لبرنامج "عشت وشفت" الذي يبث على قناة "الشروق تي في"، باعتباره من بين البرامج التي تسلط الضوء على قصص واقعية ترتبط بالعنف الأسري وتعرضها للمتلقي بأسلوب درامي – توثيقي. وقد تم تنظيم الدراسة ضمن ثلاثة محاور رئيسية: 1. الإطار المنهجي: حيث تم عرض الإشكالية، والتساؤلات، والفرضيات، والأهداف، والمنهج المعتمد، إضافة إلى أدوات جمع البيانات والعينة المدروسة والنظرية التفسيرية المعتمدة. 2. الإطار النظري: وتناول الجوانب المتعلقة بالتلفزيون والبرامج التلفزيونية من جهة، والمعالجة الإعلامية لظاهرة العنف الأسري من جهة أخرى، من خلال استعراض البنية المفاهيمية، والأنواع، وأشكال التأثير، إلى جانب الخلفية الاجتماعية والنفسية للعنف الأسري. 3. الإطار التطبيقي: وكرّس لتحليل مضامين مختارة من حلقات برنامج "عشت وشفت"، للكشف عن الكيفية التي يُعالج بها العنف الأسري في هذه الحلقات، والرسائل الضمنية التي تُوجَّه للجمهور، ومدى مساهمة هذا النوع من البرامج في التوعية والتحسيس بخطورة هذه الظاهرة. وترتكز الدراسة على جملة من المفاهيم النظرية، على غرار نظرية التأثير الإعلامي، ونظرية الإشباع، ونظرية التنشئة الاجتماعية، مع استحضار دراسات سابقة قاربت نفس الموضوع في السياقين المحلي والدولي. وتتوصل هذه الدراسة إلى أن البرامج التلفزيونية قادرة، إذا أُحسن توجيهها، على لعب دور فعال في رفع مستوى الوعي المجتمعي، وتفكيك البنى الثقافية التي تشرعن العنف، وتقديم نماذج بديلة للتعامل داخل الأسرة. غير أن هذا الدور يظل مرهونًا بمدى التزام القائمين على تلك البرامج بالضوابط الأخلاقية والمهنية، وبقدرتهم على الموازنة بين الإثارة الإعلامية والرسالة التوعوية. الكلمات المفتاحية : البرامج التليفيزيونية,المعالجة , العنف الأسري Dissertation Summary This dissertation explores the role of television as a social tool in addressing one of the most sensitive and pressing issues in contemporary Algerian society: domestic violence crimes. The study specifically focuses on the program “Aasht W Shaft” broadcast by Echorouk TV, as a case study to analyze how television programming portrays and attempts to deal with this phenomenon. The central research problem revolves around the following question: To what extent can television programs contribute to the prevention and treatment of domestic violence within Algerian society? This led to a series of sub-questions and hypotheses related to the effectiveness of televised content, its narrative strategies, and its impact on public awareness and social change. The theoretical framework of the study is based on two main axes. The first addresses television as a medium, tracing its development, functions, and the different formats of TV programs, especially in Algeria. The second axis explores the phenomenon of domestic violence, analyzing its definitions, root causes, and psychological, legal, and social consequences. In the practical part, the study applies qualitative content analysis to selected episodes of the show “Aasht W Shaft.” These episodes were chosen based on their relevance to the topic and their representational diversity. The analysis revealed that the show adopts a documentary-dramatic approach that combines real testimonies with emotional storytelling, aiming to raise awareness and provoke public debate on taboo issues. Among the major findings of the study is that television programs in Algeria have begun to break the culture of silence surrounding domestic violence, offering victims a platform to share their stories and challenging societal norms that normalize abuse. However, the study also noted limitations, including sensationalism in some episodes, insufficient expert intervention, and a lack of long-term follow-up on featured cases. The dissertation concludes that while television has significant potential to contribute to the fight against domestic violence, its impact depends largely on how responsibly and professionally it is used. The study recommends strengthening collaboration between media institutions and social/legal bodies, offering specialized training for journalists on how to handle sensitive issues, and developing ethical guidelines for the media representation of victims. In essence, this research affirms the transformative power of media when aligned with social responsibility, and highlights the need for a more strategic and interdisciplinary approach to media-based interventions in social issues. Keywords: Television programs, intervention, domestic violence
دراسة تحليلية لحلقات من برنامج" عشت و شفت"